1996
DOI: 10.1089/dna.1996.15.989
|View full text |Cite
|
Sign up to set email alerts
|

A Single Expression Site with a Conserved Leader Sequence Regulates Variation of Expression of thePneumocystis cariniiFamily of Major Surface Glycoprotein Genes

Abstract: The major surface glycoprotein (MSG) of Pneumocystis carinii is encoded by a family of related but distinct genes distributed throughout the P. carinii genome. Previous reports of the genomic and mRNA MSG structure suggested that there was a highly conserved 5'-untranslated region and a highly variable translated region. In the current study, we demonstrate that there is a single expression site for MSG expression and that different MSG genes are located downstream of this expression site. Isolation of a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…carinii would be heterogeneous in structure at points downstream of the UCS and that these downstream regions might differ between populations. Mapping of restriction enzyme cleavage sites downstream of the UCS produced results consistent with this prediction (31,146). The downstream heterogeneity of the UCS locus was consistent with the previously observed presence of mRNAs encoding different MSG isoforms, yet each starting with a copy of the UCS.…”
Section: Msg Gene Transcriptssupporting
confidence: 87%
See 2 more Smart Citations
“…carinii would be heterogeneous in structure at points downstream of the UCS and that these downstream regions might differ between populations. Mapping of restriction enzyme cleavage sites downstream of the UCS produced results consistent with this prediction (31,146). The downstream heterogeneity of the UCS locus was consistent with the previously observed presence of mRNAs encoding different MSG isoforms, yet each starting with a copy of the UCS.…”
Section: Msg Gene Transcriptssupporting
confidence: 87%
“…The divergent sequences downstream of the UCS encoded different isoforms of MSG. These findings were confirmed by another group using a similar approach (31).…”
Section: Msg Gene Transcriptssupporting
confidence: 66%
See 1 more Smart Citation
“…Molecular examination of Msg genomic localization and expression revealed that the msg gene undergoes extensive genomic rearrangement, resulting in variations in its antigenic properties (148,161,203,280,281). The expressed msg gene copy is positioned at a specific expression site in the genome, with a single protein isoform expressed at one time (73,283,305). Variation of the Msg protein appears to occur through transcriptional regulation and involves complex genomic rearrangement resulting in variant expression of msg genes.…”
Section: Pneumocystis Antigensmentioning
confidence: 99%
“…Transcribed MSG messengers always contained an upstream conserved sequence (UCS) (Edman et al 1996;Sunkin & Stringer 1997;Wada & Nakamura 1996;Wada et al 1995), which has only one copy in the P. carinii genome (Edman et al 1996;Wada et al 1995), suggesting that MSG is transcribed from a specific expression site marked with the unique UCS element. In addition, translation initiation codon on an MSG mRNA is located in the sequence transcribed from the UCS (Edman et al 1996;Wada et al 1995). Therefore, transcribing MSG from UCS-containing expression site is essential for proper MSG translation.…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 99%